PERAN DINAS TENAGA KERJA DALAM MENGATASI TINGKAT PENGANGGURAN PADA MASA PANDEMI COVID-19 DI KOTA BATAM - Manurung, Junita Marlina; Sibarani, Timbul Dompak (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to describe the impact Pandemic Covid-19 of March, 2019 in Indonesia. Covid-19 has had an impact on the employment sector. Researcher describe the role of the Batam City Manpower Office in an effort to overcome the unemployment rate in Batam City. The role of the Batam City Manpower Office is to make policies, implement programs to increase workforce competence, facilitate public access to job information, and provide training to the community to become young entrepreneurs. Map out the factors that influence the role of Manpower Office in carrying out its duties and functions. The type of research approach used by the researcher is a qualitative descriptive approach with data collection methods through interviews, observation and documentation. The results of this study indicate that the Batam City Manpower Office has attempted to overcome unemployment during the Covid-19 pandemic through policy programs even though its implementation has limited human resources and budget constraints. The Batam City Manpower Office has the responsibility to carry out training programs properly in order to produce quality, productive, effective and efficient workers so that they can compete with the industrial and business world. Keywords : Batam City Manpower Office, Role, Manpower, Covid-19